(untitled) - Fingleton, Eamonn (New York, 1995)
Contents: Sayonara, capitalism, hidden strengths, the will to win, the invisible leviathan,...
Keywords: Economic forecasting,Dự báo kinh tế; Japan,Nhật Bản